A genome-wide survey of DNA methylation in hexaploid wheat. Issue 1 (December 2015) - Gardiner, Laura-Jayne; Quinton-Tulloch, Mark; Olohan, Lisa; Price, Jonathan; Hall, Neil; Hall, Anthony
Abstract Background DNA methylation is an important mechanism of epigenetic gene expression control that can be passed between generations. Here, we use sodium bisulfite treatment and targeted gene enrichment to study genome-wide methylation across the three sub-genomes of allohexaploid wheat. Results While the majority of methylation is conserved across all three genomes we demonstrate that differential methylation exists between the sub-genomes in approximately equal proportions. We correlate sub-genome-specific promoter methylation with decreased expression levels and show that altered growing temperature has a small effect on methylation state, identifying a small but functionally relevant set of methylated genes. Finally, we demonstrate long-term methylation maintenance using a comparison between the D sub-genome of hexaploid wheat and its progenitorAegilops tauschii . Conclusions We show that tri-genome methylation is highly conserved with the diploid wheat progenitor while sub-genome-specific methylation shows more variation.